Scaffolding the Learning Opportunities: Academic Integrity at Douglas College - Salmon, Holly; Tilley, Janette (Canadian Perspectives on Academic Integrity, 2021)
Douglas College has recently developed a wrap-around (multi-touchpoint) model of student education for academic integrity at the college. This presentation will share the preliminary work being done, both college-wide and discipline-specific, including a recent policy language update to encourage faculty to consider whether an academic integrity issue might be regarded as a learning opportunity, rather than a violation. It will also provide a snapshot of preliminary data collected about students being reported in one of the divisions at Douglas. The key educational points for students include opportunities for learning, both mandatory and optional: academic integrity workshop at orientation completion of an academic integrity module on blackboard for all new students new tailored learning modules for Arts and Business programs resources and in-class instruction from the library tutoring sessions from the Learning Centre with peer tutors a new student-facing website (FAQ) The first contacts for learning are within the students first few weeks and organized by the college, program or instructor, while the Learning Centre sessions are directly booked by students by selecting from three academic integrity topics: Understanding and Awareness, Using Sources in Your Writing, Style and Formatting Guidelines. In these appointments, students build on previous understanding of academic integrity, learn about resources available, and develop plans to continue their learning. Writing appointments also aid students to focus on developing paraphrasing skills and ability to use sources as evidence in writing assignments, how to find the formatting and style rules needed for assignments, as well as what aspects of the style and formatting are important in most college assignments. We’ll also outline possible next steps at Douglas, including understanding learning effectiveness and increased collaboration between Faculties.